Clinicians' Perspectives on Admission of Pregnant Women: A Triad. Issue 5 (September 2019) - Breman, Rachel Blankstein; Iobst, Stacey; Paul, Julie; Low, Lisa Kane
Abstract: Purpose: Reducing primary cesarean births is a national priority in the United States. Recommendations include delaying admission of low-risk pregnant women to the hospital until they are in active labor, considered to be 6 cm cervical dilatation. How this recommendation affects decision-making during triage requires further exploration. The purpose of this study was to explore the clinician's perspective on the triage process and deferral of hospital admission for low-risk pregnant women who were not yet in active labor. Methods: A qualitative descriptive approach was used via semistructured interviews with physicians, midwives, and nurses. Data analysis used an inductive approach and identified codes, a theme and subthemes. Results: Twenty-five clinicians participated. A triad of decision-making occurred between three main stakeholders: the low-risk pregnant woman, the triage nurse, and the physician or midwife. One theme and four subthemes related to this triad were identified. The theme Admission of Low-Risk Pregnant Women Depends on Many Factors provides context to the maternity care triage process. There are many factors clinicians consider prior to admitting women, including situational and clinical factors. Subthemes related to the woman are her expectation and knowledge about birth and her ability to cope with labor. Subthemes associated with the provider and triage nurse are care variation and concern for maternal and fetal safety. Clinical Implications: From the clinician's perspective, triage is a complex, dynamic process, even for low-risk pregnant women. There is an interplay of different factors affecting clinical decision-making, thus the decision-making triad provides a possible framework for shared decision-making. Abstract : The decision on whether to admit a low-risk woman in early labor to the hospital is complex and involves a thorough assessment and many interrelated factors. In this study, nurses, midwives, and physicians offer their thought processes and perceptions of low-risk women presenting in early labor that influence the decision for admission. As admission in latent labor has been associated with a high number of interventions and an increased risk of cesarean birth, this study has important clinical implications.